2022
DOI: 10.1002/smll.202106569
|View full text |Cite
|
Sign up to set email alerts
|

Functional Extracellular Vesicles for Regenerative Medicine

Abstract: The unique biological characteristics and promising clinical potential of extracellular vesicles (EVs) have galvanized EV applications for regenerative medicine. Recognized as important mediators of intercellular communication, naturally secreted EVs have the potential, as innate biotherapeutics, to promote tissue regeneration. Although EVs have emerged as novel therapeutic agents, challenges related to the clinical transition have led to further functionalization. In recent years, various engineering approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 180 publications
0
32
0
Order By: Relevance
“…Similarly, priming MSCs derived from adipose tissue with TNF-a results in EV secretion and osteogenic differentiation of human primary osteoblasts ( Davies et al, 2017 ; Lu et al, 2017 ; Lee and Kim, 2021 ; Liu and Holmes, 2021 ; Nagelkerke et al, 2021 ). EVs can also be bioengineered and enriched with favourable factors such as drugs and growth factors to serve as targeted therapies ( Kim et al, 2022 ). All of these demonstrate the huge potential of EVs for tissue regeneration.…”
Section: Regenerative Potential Of Extracellular Spacementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, priming MSCs derived from adipose tissue with TNF-a results in EV secretion and osteogenic differentiation of human primary osteoblasts ( Davies et al, 2017 ; Lu et al, 2017 ; Lee and Kim, 2021 ; Liu and Holmes, 2021 ; Nagelkerke et al, 2021 ). EVs can also be bioengineered and enriched with favourable factors such as drugs and growth factors to serve as targeted therapies ( Kim et al, 2022 ). All of these demonstrate the huge potential of EVs for tissue regeneration.…”
Section: Regenerative Potential Of Extracellular Spacementioning
confidence: 99%
“…To bypass some of the limitations of natural occurring EVs and avoid some of the mentioned inconsistencies, EVs can be bioengineered and enriched with favourable factors resulting in enhanced yield and better isolation but the full impact of these modifications on target cells needs to be investigated in detail ( Kim et al, 2022 ). In clinical translation, it is yet to be determined which donor cell source can provide the most potent EV subtypes and which factors influence this ( Beer et al, 2017 ).…”
Section: Challenges In Secretome Therapy For Tissue Regenerationmentioning
confidence: 99%
“…Extracellular vesicles (EVs), which are nano- to micro-sized lipid bilayer membrane particles secreted by host cells, play critical roles in novel intercellular communication mechanisms, mediating the transduction of functional molecules with physiological activity, such as microRNAs, mRNAs, proteins, and lipids ( Figure 1 ) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ,…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating studies have suggested that EVs represent a new manner of intercellular communication and contribute to the regulation of many pathophysiological processes [ 19 , 20 ]. In addition, the lipid bilayer membrane structure endows EVs with great stability in circulation and protects their cargo from degradation [ 21 ]. Recently, the cell-free strategy based on MSC-derived EVs (MSC-EVs) for tissue regeneration has attracted considerable attention.…”
Section: Introductionmentioning
confidence: 99%